2012
DOI: 10.1002/smll.201202128
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish High‐Throughput Screening to Study the Impact of Dissolvable Metal Oxide Nanoparticles on the Hatching Enzyme, ZHE1

Abstract: The zebrafish is emerging as a model organism for the safety assessment and hazard ranking of engineered nanomaterials. In this Communication, the implementation of a roboticized high‐throughput screening (HTS) platform with automated image analysis is demonstrated to assess the impact of dissolvable oxide nanoparticles on embryo hatching. It is further demonstrated that this hatching interference is mechanistically linked to an effect on the metalloprotease, ZHE 1, which is responsible for degradation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 39 publications
6
110
0
Order By: Relevance
“…In zebrafish embryos, the soluble copper released from the nano-CuO inhibits the activity of the hatching enzyme in zebrafish embryos without affecting their morphology (Lin et al, 2013). In contrast, morphology of sea urchin embryos was impacted at comparatively lower concentrations with no effect on hatching for either nano-CuO or CuSO 4 (this study); this also has been observed in Pacific herring embryos in seawater (data not shown).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In zebrafish embryos, the soluble copper released from the nano-CuO inhibits the activity of the hatching enzyme in zebrafish embryos without affecting their morphology (Lin et al, 2013). In contrast, morphology of sea urchin embryos was impacted at comparatively lower concentrations with no effect on hatching for either nano-CuO or CuSO 4 (this study); this also has been observed in Pacific herring embryos in seawater (data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…Nano-CuO has other toxic effects in aquatic organisms not related to development (Gomes et al, 2011;Hanna et al, 2014;Hanna et al, 2013;Hu et al, 2014;Lin et al, 2013). In zebrafish embryos, the soluble copper released from the nano-CuO inhibits the activity of the hatching enzyme in zebrafish embryos without affecting their morphology (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al (2012) investigated the toxicity of chromium NPs to aquatic organisms using D. rerio. This study has indicated that Cr 2 O 3 NPs could interfere with embryo hatching by a chelator-sensitive mechanism that involves ligation of critical histidine in the ZHE1 (metalloprotease, responsible for degradation of the chorionic membrane) center by the shed metal ions.…”
Section: Mv)mentioning
confidence: 99%
“…However, studies published in the international literature on the toxicity of these types of NPs to aquatic organisms are scarce. Lin et al (2012) (Knie & Lopes, 2004;Paschoalino et al, 2010). Furthermore, daphnids are considered a keystone species in aquatic toxicology because they are filter-feeders and are able to ingest NPs (Artal et al, 2013).Tests employing Daphnia have been used to evaluate the nanomaterials ecotoxicity, due to be important links in the food chain from algae consumed by them, and the fish that are predators (Paschoalino et al, 2010).They have also been proposed as a model organism for the ecotoxicological testing of nanomaterials (Paschoalino et al, 2010;Artal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%